Bilateral Optic Neuritis in a Patient with Enteric Fever: A Case Report - Chhetri, Sundip Dware; Vaidya, Keepa; Lamichhane, Suman; Rajbhandari, Sudeep Lal; Katwal, Shailendra (Nepalese Journal of Ophthalmology, 2023)
Background: Bilateral optic neuritis following enteric fever is a rare condition requiring early evaluation by an ophthalmologist and prompt treatment for visual rehabilitation. Case: A 31-year-old female diagnosed with enteric fever presented to the Neuro-ophthalmology department with sudden painful loss of vision in both eyes for 10 days. Observations: Her Best Corrected Visual Acuity (BCVA) was counting fingers close to face in left eye and 6/18 in right eye. Posterior segment examination showed blurring of disc margin on both eyes. On Magnetic Resonance Imaging (MRI) of brain and orbit there was mild thickening of retro-orbital portions of both optic nerves. She was started on steroid therapy which resulted in marked improvement of vision in both eyes. Conclusion: Optic neuritis following enteric fever is a rare entity and requires early diagnosis with prompt treatment for improvement of visual acuity and prevention of visual impairment.